Fungsi Keluarga dalam Persepektif Alkitab sebagai Basis Pendidikan Agama Kristen - Andreas Sese Sunarko (Sekolah Tinggi Teologi Kadesi Yogyakarta, 2021)
The family is an institution of God Himself (Genesis 2:18-25) aside from the church (Matthew 16:18) obtaining a glorious mandate through God's family to want the birth of Divine offspring (Malachi 2:15), which is a God-fearing and living in its prescribed streets. To achieve the above goal, a Christian Religious Education of faith became something very important. But unfortunately there are Christian families who are unaware of this and are shifting this glorious mandate to the church through sunday school teachers or transferring it to school (through Christian religious teachers). The writer assesses this distraction on the one hand as a parent's misunderstanding of the mandate or on the other hand because of the parents' inability to handle it. The method the writer uses is a descriptive qualitative with a library approach. The writer tapped relevant resources from the bible, books and journals. Starting with a general understanding and juridis about the family, the Biblical basis of the family and its calling, the family's responsibility for Christian Religious Education and the danger of displacing the function of Christisn Religious Education on the third hand and the writer will eventually conclude that it is important to restore the family's function as a base of Christian Religious Education as well as to accord with scriptural values to be so effective in reaching the goal of bearing Divine offspring.